MEMBANGUN JEMBATAN BUDAYA DALAM SAINS: PENGEMBANGAN MEDIA INTERAKTIF BERBASIS CULTURALLY RESPONSIVE TEACHING PADA MATERI TATA SURYA DI SEKOLAH DASAR KABUPATEN NABIRE - Stenly Sengkey (Journal of Education Papua Baru, 2026)
Abstract: This article condenses a thesis-based research and development study on culturally responsive interactive learning media for elementary science learning in Nabire Regency, Papua. The study was motivated by students' difficulties in understanding abstract Solar System concepts, the dominance of conventional instruction, limited contextual media, and the need to connect science learning with local cultural experience. The product was developed using the ADDIE model, consisting of analysis, design, development, implementation, and evaluation. The media, created with Articulate Storyline 360, integrates Papuan local wisdom, visual narratives, simulations, interactive quizzes, and Culturally Responsive Teaching principles. Expert validation showed that the product was highly feasible in terms of content, media, and language, with mean scores of 4.75, 4.80, and 4.65, respectively. Field testing indicated that the media was practical for students and teachers, with mean scores of 4.50 and 4.40. The effectiveness test demonstrated a substantial increase in students' conceptual understanding, from a pre-test mean of 45.25 to a post-test mean of 85.75, with an N-Gain of 0.74 in the high category and a significant difference at p < 0.001. Qualitative findings also showed stronger engagement, cultural pride, and more active participation. The article argues that culturally responsive digital media can become a bridge between scientific abstraction and local meaning in elementary education. Keywords: Culturally Responsive Teaching; interactive learning media; Articulate Storyline 360; local wisdom; Solar System; elementary science   Abstrak: Artikel ini meringkas penelitian pengembangan berbasis tesis tentang media pembelajaran interaktif yang responsif budaya pada pembelajaran IPA sekolah dasar di Kabupaten Nabire, Papua. Kajian ini dilatarbelakangi oleh kesulitan peserta didik memahami konsep Tata Surya yang abstrak, dominasi pembelajaran konvensional, keterbatasan media kontekstual, serta kebutuhan menghubungkan pembelajaran sains dengan pengalaman budaya lokal. Produk dikembangkan melalui model ADDIE yang mencakup tahap analisis, desain, pengembangan, implementasi, dan evaluasi. Media yang dibuat dengan Articulate Storyline 360 mengintegrasikan kearifan lokal Papua, narasi visual, simulasi, kuis interaktif, dan prinsip Culturally Responsive Teaching. Hasil validasi ahli menunjukkan media sangat layak dari aspek materi, media, dan bahasa dengan skor rata-rata berturut-turut 4,75, 4,80, dan 4,65. Uji coba lapangan menunjukkan media praktis digunakan oleh peserta didik dan guru dengan skor rata-rata 4,50 dan 4,40. Efektivitas media tampak dari peningkatan pemahaman konsep dari rata-rata pre-test 45,25 menjadi post-test 85,75, nilai N-Gain 0,74 pada kategori tinggi, serta perbedaan signifikan pada p < 0,001. Temuan kualitatif menunjukkan meningkatnya keterlibatan, kebanggaan budaya, dan partisipasi aktif peserta didik. Artikel ini menegaskan bahwa media digital responsif budaya dapat menjadi jembatan antara konsep ilmiah yang abstrak dan makna lokal dalam pendidikan dasar. Kata kunci: Culturally Responsive Teaching; media pembelajaran interaktif; Articulate Storyline 360; kearifan lokal; Tata Surya; IPA sekolah dasar